Kajian Yuridis Terhadap Perkawinan dibawah Umur - Rahajaan, Jakobus Anakletus; Niapele, Sarifa (Public Policy, 2021)
Abstract Conducted research related to underage marriage, namely in the form of a juridical review using normative legal research methods, which analyze the provisions of laws and regulations related to the minimum age limit for a person. who can be granted permission to carry out the marriage. The results of our research can be abstracted as follows: Marriage is a very important and even sacred event in human life. A legal marriage, the requirements, among others, must meet the principle of consensualism or agreement (agreement) of the parties, as stated in article 6 paragraph 1 of the Marriage Law which reads, "Marriage must be based on the consent of the two prospective brides". furthermore according to Article 7 paragraph 1 of Law no. 1 of 1974 as amended by Law No. 16 of 2019 which requires that a marriage is legal if allowed by the parents of the parties, if the man and woman have reached the age of 19 years. The provisions of the Compilation of Islamic Law (KHI), article 15 paragraph 1 have not been adjusted to the provisions of Article I of Law no. 16 of 2019 concerning amendments to Law no. 1 of 1974, article 7 paragraph 1, will remain a problem that has the potential to violate the law, namely underage marriage as a marriage which is considered illegal based on the provisions of Law No. 16 of 2019. For this reason, policy makers in this republic must be able to immediately uniform or To harmonize various regulations regarding the adult age limit of a child and in particular the minimum age limit for people who wish to marry, at least, the provisions of Article 15 paragraph 1 of the KHI must be immediately revised and adjusted to the provisions of Article I of Law No.16 of 2019 concerning amendments to Article 7 paragraph 1 of Law No.1 of 1974 concerning Marriage, so that the legal layman can more clearly understand the meaning of the latest statutory provisions regarding the minimum age of 19 years for the prospective bride. Keywords: Judicial Review, Marriage, Underage